Penerapan Panel Surya dan Cross Ventilation pada Desain Pusat Pembangkit Listrik Tenaga Sampah (PLTSa) di Makassar - Mirdawati, Mirdawati; Marwati, Marwati; Herniwati, Andi (TIMPALAJA : Architecture Student Journals, 2024)
Electricity has become society's primary need, which will continue in the future, along with the increasing use of electrical equipment. The need to utilize electrical energy is so significant that it differs from conventional power plants in terms of the availability of energy sources. Conventional electrical energy sources come from fossil fuels, which are the largest source of pollution that has an impact on global warming. This research aims to minimize global warming and support energy procurement using solar panels, using a qualitative descriptive method by identifying the use of solar panels and cross ventilation systems in the design of the Waste Power Plant Center in Makassar City, followed by a comparative study. The design result is the application of monocrystalline solar panels with a slope of 15° and a cross-ventilation system with bottom casement-type openings installed with wide openings to optimize airflow circulation.